Body image concerns and disordered eating among older women: Identifying variables of interest for integrated models. Issue 7 (29th January 2022) - Rodgers, Rachel F; Berry, Rachel A; Laveway, Katherine
Abstract: Objective: Research focused on developing risk and protective models of body image concerns and disordered eating among older women is scant. Models including biological, psychological, and sociocultural elements may be useful explanatory frameworks in this group. Thus, the aim of this study was to conduct formative research exploring the constructs that form part of biopsychosocial models of body image concerns and disordered eating among older women. Method: A sample of 184 women aged 60–75 years completed an online survey assessing media pressures, thin‐ideal internalization, depression symptoms, weight and shape concerns, and disordered eating as well as positive reappraisal and acceptance of aging‐related changes to appearance. Results: After the addition of two supplemental pathways, the model revealed good fit to the data. In the final model, age, depression, and media pressure were associated with media internalization, that was in turn associated with weight and shape concerns, and then disordered eating. Depression was also directly associated with both weight and shape concerns and disordered eating. The model varied across older women with high versus low levels of positive reappraisal and acceptance of aging‐related changes to appearance. Specifically, among those high on this trait, the pathways between depression and thin‐ideal internalization, and between weight and shape concerns and disordered eating were significantly weaker. Discussion: These findings support the usefulness of biopsychosocial models for grounding research on body image concerns and disordered eating among older women, and suggest positive reappraisal and acceptance of aging‐related changes to appearance as a useful dimension to focus on.